The Relationship between Childhood Maltreatment and Non-Suicidal Self-Injury: A Systematic Review - Serafini, Gianluca; Canepa, Giovanna; Adavastro, Giulia; Nebbia, Jacopo; Belvederi Murri, Martino; Erbuto, Denise; Pocai, Benedetta; Fiorillo, Andrea; Pompili, Maurizio; Flouri, Eirini; Amore, Mario (Frontiers in Psychiatry, 2017)
Introduction: Childhood maltreatment (CM) has been associated with an increased risk of non-suicidal self-injury (NSSI) and suicidal behaviors. However, the exact nature of the association between CM and NSSI is currently unclear. The present review aimed to systematically investigate the association between CM and NSSI in adolescence and early adulthood. Methods: A systematic search of four major electronic databases covering both medical and social science research (PubMed, Scopus, Science Direct, and PsycINFO) was conducted. Results: Overall, 20 cross-sectional studies including a total of 22,517 individuals, 3 longitudinal follow-up studies including 1,728 individuals, and 3 retrospective studies including 62,089 individuals were selected. It appears that CM is a significant risk factor for both NSSI and suicide attempts. The increased vulnerability to NSSI seems to be related to experiences of childhood maltreatment, particularly sexual abuse. Gender differences were also found. Generally, when compared to males, females who experienced CM seem to be more vulnerable to presenting with NSSI and suicidal behaviors. Conclusion: There is a positive association between CM and NSSI. The importance of early detection and risk reduction for both children and adolescents who present with self-injurious behavior is discussed.